Ultrastructure and morphometry of the egg of Psorophora albipes (Theobald, 1907) (Diptera: Culicidae) - Mello, Cecilia Ferreira De (2017)
The eggs of Psorophora albipes were studied using scanning electron microscopy (SEM) and described based on a morphometric analysis of the main structures observed. We used eggs from a female caught in the Poço das Antas Biological Reserve (REBIO-PA), located in the municipality of Silva Jardim, State of Rio de Janeiro, Brazil. The eggs have an elliptical outline with a mean length of 538.67 ± 69.89 µm and width of 157.66 ± 23.12 µm and a mean egg index of 3.42 ± 0.07 µm. The external coating of the eggs is regular, with elongated chorionic cells that vary in size, with a mean length of 13.02 µm and mean width of 6.47 µm. The cells mostly have a pentagonal shape, but some have an elliptical shape. The micropylar disc has a mean diameter of 19.8 µm, it has small irregularities in its outline, excavations at the edge with the center slightly raised and a micropyle with a diameter of 2.36 µm. Complete knowledge of the egg morphology of species through SEM is useful in correlating its fine structure with consistent non-discernible differences observed under a stereoscopic microscope, and can aid in species discrimination. SEM allows the construction of identification keys for mosquito eggs that should be useful for studies involving eggs recovered from ovitraps or debris/soil samples.